2022
DOI: 10.1080/14686996.2022.2146466
|View full text |Cite
|
Sign up to set email alerts
|

Impact of spontaneous liposome modification with phospholipid polymer-lipid conjugates on protein interactions

Abstract: Liposome surface coating has been studied to avoid the immunological responses caused by the complement system, and alternative materials to poly(ethylene glycol) (PEG) have been explored recently since the production of anti-PEG IgM antibodies has been found in humans. We previously reported a liposome coating with poly(2-methacryloyloxyethyl phosphorylcholine) (poly(MPC))-conjugated lipids (PMPC-lipids) and demonstrated its protective effect on blood protein interactions. Here, we attempted to modify the lip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…This suggested that the liposomes could be modified via external modification, where liposome surfaces are modified by exogenously mixing fHep-lipids with liposomes. 41 The long-term stability of the modified liposomes was also monitored over a period of 90 days, and no changes in size (Fig. 4D), PDI (Fig.…”
Section: Characterization Of Modified Liposomesmentioning
confidence: 97%
“…This suggested that the liposomes could be modified via external modification, where liposome surfaces are modified by exogenously mixing fHep-lipids with liposomes. 41 The long-term stability of the modified liposomes was also monitored over a period of 90 days, and no changes in size (Fig. 4D), PDI (Fig.…”
Section: Characterization Of Modified Liposomesmentioning
confidence: 97%
“…56−58 Moreover, PMPC-LPs demonstrated no interaction with the anti-PEG IgM antibody. 54,59 Recently, Adler et activators regenerated by electron transfer for atom transfer radical polymerization (ARGET-ATRP) method and coated LPs with 1−10 mol % PMPC−lipids. 60 The presence of PMPC−lipids on LPs can significantly reduce protein adsorption in human plasma and blood and became more effective as the molecular weight and molar ratio of the PMPC−lipids increased.…”
Section: ■ Introductionmentioning
confidence: 99%
“…PMPC coating onto the surface of LPs can effectively prevent the adsorption of human complement protein C3 (C3), a key protein in the complement system . When C3 binds to a surface, it can initiate complement activation through an alternative pathway and then triggers recognition by complement receptors present on phagocytic cells. Moreover, PMPC-LPs demonstrated no interaction with the anti-PEG IgM antibody. , Recently, Adler et al. synthesized PMPC–lipid (C18) pairs using PMPC molecules of various polymerization degrees, including 10 (MPC10–lipid), 20 (MPC20–lipid), 50 (MPC50–lipid), and 100 (MPC100–lipid), via the activators regenerated by electron transfer for atom transfer radical polymerization (ARGET-ATRP) method and coated LPs with 1–10 mol % PMPC–lipids .…”
Section: Introductionmentioning
confidence: 99%